Penerapan Metode Demontrasi Dalam Meningkatkan Prestasi Belajar IPA Pada Kelas VI SDN Tarusan Danum - patent patent (Jurnal Ilmiah Kanderang Tingang, 2022)
This study aims to improve student achievement in science subjects, especially material change objects through the application of the demonstration method at Tarusan Danum Elementary School, Tewang Sagalang Garing District, Katingan Regency. Based on internal observations, grade VI students have poor learning outcomes where the average value obtained before knowing this research is 57.083% and the percentage of students who achieve learning completeness standards is 50%. This Classroom Action Research (CAR) was conducted for two months using the demonstration method in an effort to improve the science learning achievement of sixth graders at SDN Tarusan Danum. This research was conducted through two cycles where each cycle consisted of two meetings through several stages, namely planning, observation and reflection. Data collection techniques were carried out using observations of each meeting by observers and learning outcomes from the value of students' exercises in each cycle. Based on research conducted for two cycles, the results obtained are, in the first cycle of 57.5% and in the second cycle of 70.5%.